2017
DOI: 10.1002/ange.201711658
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Unstrained C−C Bonds in Acenes by Boron and Light: Transformation of Naphthalene into Benzoborepin

Abstract: Naphthalene and acenaphthene with peri 2-pya nd BMes 2 (py = pyridyl, Mes = mesityl) substituents have been found to undergo facile phototransformation, cleavage of a CÀCb ond of naphthalene,a nd formation of 2-py-bound benzoborepins as the major products.Mechanistic pathways of this photoreaction have been established by examination of both excited and ground states by using CASSCF and CASPT2 methods in DFT and time-dependent DFT calculations.T he mesityl to py-naphthyl charge-transfer transition and the mesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…The B−N and B−C bond distances fall in the range 1.646(3)−1.669(2) and 1.583(3)− 1.626(3) Å, respectively (Table 1), which are consistent with the values reported in the literature for B←N coordinated boron complexes. 9,11,16 The molecular structures of all the compounds showed that the boron atom coordinates to the pyridyl nitrogen atom to form a five-membered ring (Figure 1). The Ar group attached to pyridyl becomes coplanar due to B←N coordination.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…The B−N and B−C bond distances fall in the range 1.646(3)−1.669(2) and 1.583(3)− 1.626(3) Å, respectively (Table 1), which are consistent with the values reported in the literature for B←N coordinated boron complexes. 9,11,16 The molecular structures of all the compounds showed that the boron atom coordinates to the pyridyl nitrogen atom to form a five-membered ring (Figure 1). The Ar group attached to pyridyl becomes coplanar due to B←N coordination.…”
Section: ■ Results and Discussionsupporting
confidence: 63%
“…Aside from the direct use of base-stabilized boriranes in materials science, these high energy species can also be used as reactive intermediates in the facile preparation of functional materials such as singly annulated borepins [56] and chiral N,B,X-heterocycles (X = S or O) [57]. Borepins are charge neutral, boron-containing analogues of the tropylium cation, where the boron atom is typically protected by bulky substituents [58].…”
Section: Boriranes As Reactive Intermediates Towards Luminescent Matementioning
confidence: 99%
“…34 Structure A is prepared by a modular synthetic approach and shows helical chirality. The Wang group introduced structure B, showing interesting photochemical reactivity, 35 similar to earlier systems that were based on ( ppy)BMes 2 ( ppy = 2-phenylpyridine). 28 Substituting the pyridyl unit with an isoquinolyl enabled our group to design arylisoquinolinederived fluorophores with naphthyl (structures C with varying electron-donating substituents R) or anthryl (structure D).…”
Section: Introductionmentioning
confidence: 83%